Application of metagenomics next-generation sequencing of pathogen in patients with pneumonia-induced sepsis - XU Feixiang; YU Feng; WANG Ruilan; SONG Zhenju; TONG Chaoyang; ZHU Changqing (Shanghai Jiaotong Daxue xuebao. Yixue ban)
Objective·To explore the diagnostic, therapeutic, and prognostic value of metagenomics next-generation sequencing (mNGS) in patients with pneumonia-induced sepsis.Methods·This study consisted of a multicenter, prospective, non-randomized controlled trial and a diagnostic test. Patients with pneumonia-induced sepsis who were hospitalized in four hospitals across China were enrolled between March 2020 and October 2021. All patients met the Sepsis-3 criteria issued by the Society of Critical Care Medicine and the European Society of Intensive Care Medicine, as well as the clinical diagnostic standard of pneumonia. Enrolled patients were assigned based on their preference to either the conventional test-only group [receiving only conventional test (CMT)] or the combined mNGS test group (receiving CMT and mNGS concurrently). The primary outcome was the 7-day all-cause mortality rate, and secondary outcomes included the changes in SOFA and APACHE Ⅱ scores from baseline to day 7, 28-day all-cause mortality rate, the composite endpoint of mechanical ventilation or death within 28 d, 28 d ventilation-free days, 28 d hospital-free days, and the average daily hospitalization cost. Propensity score matching was used to balance covariates between the two groups. Kaplan-Meier curves were plotted and Cox proportional hazards models were built to compare the risk of death between the two groups. Pathogen detection results from infection site samples in the combined mNGS test group were used for the diagnostic test. The clinically-adjudicated causative pathogens was used as the reference standard. The results of traditional pathogen detection and mNGS detection were compared respectively with the reference standard. The positive percent agreement, negative percent agreement, positive predictive value, and negative predictive value between the two methods and the reference standard were calculated. McNemar's χ2 test was used to evaluate the causative pathogen detection capabilities of the two methods.Results·A total of 533 patients were enrolled, of whom 311 opted for additional mNGS testing, while 222 received only conventional pathogenetic testing. In the non-randomized controlled trial, after propensity score matching to balance covariates, the 7-day all-cause mortality was lower in the combined mNGS test group compared to the conventional test-only group [4.8% vs 8.6%, HR 0.37 (95%CI 0.15‒0.91), P=0.031]. Additionally, the 28-day ventilation-free days were increased in the combined mNGS test group (19.9 d vs 18.4 d, P=0.041). No significant difference was observed between the two groups in terms of 28-day all-cause mortality or the average daily hospitalization costs. In the diagnostic test, compared to the reference standard, the positive percent agreement of mNGS with the clinical composite judgment for causative pathogens was higher than that of CMT [91.9% (95%CI 87.7%‒95.0%) vs 56.1% (95%CI 49.7%‒62.4%), P<0.001]. Conversely, the negative percent agreement of mNGS was lower than that of CMT [29.2% (95%CI 18.6%‒41.8%) vs 69.2% 95%CI 56.6%‒80.1%), P<0.001]. The negative predictive value of nNGS was higher than that of CMT [48.7%(95%CI 32.4%‒65.2%) vs 29.4% (95%CI 22.3%‒37.3%), P=0.001].Conclusion·In patients with pneumonia-induced sepsis, mNGS of infection site samples demonstrated a higher detection rate of causative pathogen compared to CMT. Furthermore, the combination of mNGS with CMT may help reduce the 7-day all-cause mortality, suggesting that mNGS has clinical value and potential for application in the management of sepsis caused by pulmonary infections.